Innovation in teaching by applying neuro linguistic programming / Muhamad Fuad Abdul Karim, Hanim Abdul Razak and Mohammad Bastyian Mahmud - Abdul Karim, Muhamad Fuad; Abdul Razak, Hanim; Mahmud, Mohammad Bastyian (UiTM Press, 2020)
NLP provides various alternatives in teaching and learning such as delivery and communication method based on basic human senses acceptance namely visual, auditory and kinesthetic. NLP application is capable in engaging enthusiasm and facilitates the learning and teaching process just as the information or knowledge has been successfully delivered, observed and understood by the student and consequently aiding an excellent academic achievement. This article discusses in brief the NLP usage to educators for an effective communication purpose and serves as the basis in introducing the advantage of using NLP during teaching and learning session. To provide exposure and as a catalyst in producing a comprehensive NLP model that focuses to the teaching and learning purpose in each IPTA and IPTS especially in Universiti Teknologi MARA.